Active surveillance and genetic evolution of avian influenza viruses in Egypt, 2016-2018 - Kandeil, Ahmed; Hicks, Joseph T.; Young, Sean G.; El Taweel, Ahmed N.; Kayed, Ahmed S.; Moatasim, Yassmin; Kutkat, Omnia; Bagato, Ola; McKenzie, Pamela P.; Cai, Zhipeng; Badra, Rebecca; Kutkat, Mohamed; et al. (Emerging microbes & infections, 2019)
Egypt is a hotspot for avian influenza virus (AIV) due to the endemicity of H5N1 and H9N2 viruses. AIVs were isolated from 329 samples collected in 2016-2018; 48% were H9N2, 37.1% were H5N8, 7.6% were H5N1, and 7.3% were co-infections with 2 of the 3 subtypes. The 32 hemagglutinin (HA) sequences of the H5N1 viruses formed a well-defined lineage within clade 2.2.1.2. The 10 HA sequences of the H5N8 viruses belonged to a subclade within 2.3.4.4. The 11 HA of H9N2 isolates showed high sequence homology with other Egyptian G1-like H9N2 viruses. The prevalence of H5N8 viruses in ducks (2.4%) was higher than in chickens (0.94%). Genetic reassortment was detected in H9N2 viruses. Antigenic analysis showed that H9N2 viruses are homogenous, antigenic drift was detected among H5N1 viruses. AI H5N8 showed higher replication rate followed by H9N2 and H5N1, respectively. H5N8 was more common in Southern Egypt, H9N2 in the Nile Delta, and H5N1 in both areas. Ducks and chickens played a significant role in transmission of H5N1 viruses. The endemicity and co-circulation of H5N1, H5N8, and H9N2 AIV coupled with the lack of a clear control strategy continues to provide avenues for further virus evolution in Egypt.